A history of western music - Burkholder, J. Peter; Grout, Donald Jay; Palisca, Claude V. (W. W. Norton, 2019)
The definitive survey, combining current scholarship with a vibrant narrative. Carefully informed by feedback from dozens of scholars, it remains the book that students and teachers trust to explain what's important, where it fits, and why it matters. Peter Burkholder weaves a compelling story of people, their choices, and the western musical tradition that emerged. From chant to hip-hop, he connects past to present to create a context for tomorrow's musicians.
Keywords: Music : History and criticism; musiikintutkimus; länsimainen kulttuuri; musiikinhistoria; sävellykset; arvottaminen; musiikkikritiikki; klassikot; taidemusiikki; säveltäjät; historia; musiikki; tyylikaudet; länsimaat